Geomechanical behaviour of uncemented expanded polystyrene (EPS) beads?clayey soil mixtures as lightweight fill - O'Kelly, Brendan (My University, 2021)
Lightweight fill can be advantageous in embankment construction for the purposes ofreducing the (i) bearing pressures on the underlying soil foundation, (ii) destabilizing moments forconstructed earthen slopes, and (iii) earth pressures acting behind retaining walls. This paper inves-tigates the merits/limitations of particulate expanded polystyrene (EPS) beads mixed with clayeysand (CS) soil as lightweight fill, considering both geotechnical and environmental perspectives. Thebench-scale geotechnical testing programme included standard Proctor (SP) compaction, Californiabearing ratio (CBR), direct shear (sheardox), oedometer and permeability testing performed on twodifferent gradation CS soils amended with 0.5, 1.5 and 3.0 wt.% EPS, investigating two nominal beadsizes equivalent to poorly-graded medium and coarse sands. Compared to the unamended soils, thecompacted dry density substantially decreased with increasing EPS beads content, from 2.09 t/m3(0 wt.% EPS) to as low as 0.33 t/m3for 3 wt.% (73 v.%) of larger-sized EPS beads. However, fromanalyses of the test results for the investigated 50 to 400 kPa applied stress range, even 0.5 wt.%(21 v.%) EPS beads caused a substantial mechanical failure, with a drastic decay of the CBR andcompressibility parameters for the studied CS soils. Given the more detrimental environmental costof leaving myriads of separate EPS beads mixed forever among the soil, it is concluded that theapproach of adding particulate EPS beads to soils for producing uncemented lightened fill shouldnot be employed in geotechnical engineering practice.
PUBLISHED
Part of the Special Issue: Soil-Water-Structure Interaction
Keywords: Compaction; Compressibility; Expanded polystyrene; EPS beads; Geofoam; Lightenedfill; Strength; Smart & Sustainable Planet; COMPACTION; Environmental Geotechnics; GEOTECHNICAL ENGINEERING; Geotechnics; POLYSTYRENE; SOIL CONTAMINATION; SOIL DEFORMATION; SOIL MODIFICATION; SOIL PROPERTIES; Soil Mechanics; Soil Mechanics & Foundations; expanded Polystyrene (EPS); geotechnical; lightweight fill